Energy security and the OSCE: The case for energy risk mitigation and connectivity - Kirsten Westphal; Katja Yafimava; Indra Øverland; Ellen Scholl (Stiftung Wissenschaft und Politik (SWP), 2016)
The 2016 German Chairmanship of the Organization for Security and Co-operation in Europe (OSCE) comes at a time of increasing awareness about the interdependence between energy security and hard, economic, and human security. Energy risks are endemic in the OSCE area. Because these risks have an impact on regional security, there are good reasons for the OSCE to assume a stronger role in addressing energy security issues and reducing energy risks in the OSCE area. In so doing, the OSCE can utilise its existing capabilities in the areas of awareness-raising, early warning, prevention, mitigation, and crisis management and can build on its missions, tools, and field presence. Furthermore, the OSCE's focus on connectivity can contribute towards reducing energy risks arising from outdated or insufficient infrastructure by addressing physical connectivity jointly with legal and regulatory compatibility to improve the investment climate and foster stable policy frameworks. (SWP Comments)
Keywords: 320